Natural Resources & Income Inequality: The Role of Ethnic Divisions. - Fum, R; Holder, R (OxCarre, 2009)
We hypothesize that natural resources raise income inequality in ethnically polarized societies, but reduce income inequality in ethnically homogenous societies; and we present empirical evidence in support of this hypothesis.